Polyisobutylene‐based polyurethanes X: PU nanocomposites with s‐containing soft segments. Issue 17 (20th May 2016) - Nugay, Nihan; Toth, Kalman; Kekec, Nur Cicek; Nugay, Turgut; Kennedy, Joseph P.
ABSTRACT: Sulfur‐containing polyisobutylene (PIB)‐based polyurethane nanocomposite (PIBs ‐PU/NC) was synthesized using HOCH2 CH2 SPIBSCH2 CH2 OH for the soft segment, conventional hard segments of MDI and BDO, and organically modified montmorillonite (OmMMT) nanolayers. The properties of PIBs ‐PU/NC containing 72.5% PIB and 0.5% OmMMT were studied and contrasted with unmodified PIBs ‐PU. PIBs ‐PU/NC produces colorless optically clear films exhibiting enhanced tensile strength, elongation, oxidative–hydrolytic stability, and creep resistance relative to that of PIBs ‐PU. FTIR spectroscopy indicates H bonded S atoms between soft and hard segments, and OmMMT nanolayers. DSC and XRD suggest randomly dispersed low‐periodicity crystals and urea groups between galleries. We propose that minute amounts of OmMMT nanolayers become covalently attached to polyurethane chains and beneficially affect properties by acting as co‐chain extender/reinforcing filler. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2760–2765 Abstract : This study demonstrates that incorporation of 0.5 wt % OmMMT (o rganically modifiedm ontm orillonit e, i.e., defoliated montmorillonite nanolayers carrying N + (CH3 )3 CH2 CH2 CH2 ‐NH2 modifying molecules) into PIBs ‐PU (PIB‐based PU whose soft segments are of HOCH2 CH2 ‐S‐PIB‐S‐CH2 CH2 OH) significantly enhances the static and dynamic mechanical properties, as well as the hydrolytic‐oxidative stability of this new thermoplastic elastomer. The beneficial effect of OmMMT is likely due to its function as co‐chain extender/reinforcing filler.